Pisos de vegetación de la Sierra de San Pedro Mártir, Baja California, México - Peinado, Manuel; Bartolome, Carmen; Delgadillo, Jose; Aguado, Inmaculada (Instituto de Ecología, A.C., 1994)
A description of the belts of vegetation in Sierra de San Pedro Mártir, Baja California, is made. Belts were discerned from aerial photographs and verified by field reconnaissance in which the sigmatistic phytosociological method was used. Five belts of vegetation (Inframediterranean, Thermomediterranean, Mesomediterranean, Supramediterranean and Mesotropical) are recognized in San Pedro Mártir. Every belt is defined by means of climatological parameters and dominant plant associations.